2021
DOI: 10.11591/ijphs.v10i1.20684
|View full text |Cite
|
Sign up to set email alerts
|

Mattering and life satisfaction among the quarantined adults in Malaysia during the COVID-19 pandemic

Abstract: This study aims to investigate the role of mattering, trait extraversion and perceived social inclusion in developing the sense of life satisfaction among adults who reside in Malaysia during the quarantine period amidst the Pandemic in March-June 2020. Previous studies indicated that mattering was a robust predictor of life satisfaction; however, the nature of the quarantine might have affected the perception of social inclusion among individuals with certain levels of extraversions. Therefore, we hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…Mattering was reported as a significant predictor of SWL before the pandemic [12], [15]. Consistently, a study on the formation of SWL during the lockdown in the Malaysian context reported that mattering was a robust significant predictor of SWL, partially mediated by perceived social inclusion among individuals with low and moderate levels of extraversion [16]. They also reported that the mediation did not occur among individuals with a high level of extraversion, whose levels of mattering robustly predicted the SWL.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Mattering was reported as a significant predictor of SWL before the pandemic [12], [15]. Consistently, a study on the formation of SWL during the lockdown in the Malaysian context reported that mattering was a robust significant predictor of SWL, partially mediated by perceived social inclusion among individuals with low and moderate levels of extraversion [16]. They also reported that the mediation did not occur among individuals with a high level of extraversion, whose levels of mattering robustly predicted the SWL.…”
Section: Introductionmentioning
confidence: 61%
“…Another study in the same population and time frame suggested that the formation of SWL among locked-down young adults predicted by social comparison in social media, mediated by perceived social inclusion [17]. The robustness of mattering in predicting SWL can be justified by other studies in the Malaysian MCO context, mattering was reported as a significant predictor of other components of subjective well-being, such as unconditional self-acceptance [18], hedonic well-being [19], and perceived social inclusion [16], as well as a protective factor against depressive symptoms and suicide ideation [20]. Most of the Malaysian MCO context studies had reported that SWL and other components of subjective well-being are significantly predicted by mattering.…”
Section: Introductionmentioning
confidence: 99%
“…The main focus of this current study is to examine whether unconditional self-acceptance can explain the protective property of mattering on social comparison among undergraduate students in Malaysia. Social comparison tendency became our main context, because social comparison theory, suggested that it is our primary motive to learn and compare ourselves with those around us to define the self [1]; nevertheless, the current trend indicates that when university students have the tendency to compare themselves with others, in terms of academic achievement [2], physical appearance [3], or general life satisfaction [4], [5] they would likely to develop emotional difficulties and mental health issues, such as uncontrolled anger and depression [6], [7], especially if they lack of ability to accept themselves unconditionally. In other words, abilities to unconditionally accept oneself keep the levels of happiness and well-being, positive self-esteem and optimism, as well as protect individuals from depression and anxiety [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the change of the social behavior related to this transition have been conducted in South East Asian population, and the results yielded that the transition affected us in many ways. For instance, it was reported that the reliance to social media amidst the pandemic predicts the change of the sense of social inclusion [2], the way people gauge their life satisfaction [3], work efficacy [4], and job satisfaction [5]. Furthermore, the transition from offline to online study in educational setting had been reported to alter the way students evaluate their happiness related to their education [6], selfacceptance [7], and coping mechanism towards stress or depression symptoms [8], [9].…”
Section: Introductionmentioning
confidence: 99%